Effect of phosphorus, organic and biological fertilizer on yield of mungbean (Vigna radiata) under two cropping patterns - SURYANTINI SURYANTINI (Smujo International, 2016)
Abstract. Suryantini. 2016. Effect of phosphorus, organic and biological fertilizer on yield of mungbean (Vigna radiata) under two cropping patterns. Nusantara Bioscience 8: 273-277. The research investigated the effect of phosphorus rates, organic and biological fertilizer on productivity of mungbean grown after rice (cropping pattern: rice-rice-mungbean) and after soybean (cropping pattern: rice-soybean-mungbean). Treatment was arranged in a split plot design with three replications. The main plots were (i) without organic and biological fertilizer, (ii) organic soil treatment (OST) and (iii) phosphate solubilizing biofertilizer (PSB). The subplots were phosphorus (P) fertilizer rates: 0, 100, 150 and 200 kg SP36/ha. The results revealed that the grain yield of mungbean grown after soybean was not affected by the application of OST or PSB, but it was increased by fertilizer P at 200 kg SP36/ha with an increase of 68%, from 0.60 t/ha (control) to 1.01 t/ha. Conversely, the grain yield of mungbean grown after rice was significantly affected by the interaction between fertilizer P and OST or PSB. The highest yield was obtained from the combination treatments of 150 kg SP36/ha + PSB and 150 kg SP36/ha + OST with an increase of 78% and 71% over control respectively. Increased grain yield was supported by the increase in number of pods, 100 seeds weight, and plant P uptake.